Correction parameters in conventional dental radiography for dental implant - Barunawaty Yunus (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Radiographic imaging as a supportive diagnostic tool is the essential component in treatment planning for dental implant. It help dentist to access target area of implant due to recommendation of many inventions in making radiographic imaging previously. Along with the progress of science and technology, the increasing demand of easier and simpler treatment method, a modern radiographic diagnostic for dental implant is needed. In fact, Makassar, especially in Faculty of Dentistry Hasanuddin University, has only a conventional dental radiography. Researcher wants to optimize the equipment that is used to obtain parameters of the jaw that has been corrected to get accurate dental implant. Purpose: This study aimed to see the difference of radiographic imaging of dental implant size which is going to be placed in patient before and after correction. Method: The type of research is analytical observational with cross sectional design. Sampling method is non random sampling. The amount of samples is 30 people, male and female, aged 20–50 years old. The correction value is evaluated from the parameter result of width, height, and thick of the jaw that were corrected with a metal ball by using conventional dental radiography to see the accuracy. Data is analyzed using SPSS 14 for Windows program with T-test analysis. Result: The result that is obtained by T-Test analysis results with significant value which p<0.05 in the width and height of panoramic radiography technique, the width and height of periapical radiography technique, and the thick of occlusal radiography technique before and after correction. Conclusion: It can be concluded that there is a significant difference before and after the results of panoramic, periapical, and occlusal radiography is corrected.